2018
DOI: 10.1021/acsomega.8b02223
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Doped Silver Sulfide: An Efficient Air-Stable Electrocatalyst for Hydrogen Evolution from Neutral Water

Abstract: A low-cost, platinum-free electrocatalyst for hydrogen (H 2 ) generation via the water splitting reaction holds great promise to meet the demand of clean and sustainable energy sources. Recent studies are mainly concerned with semiconducting materials like sulfides, selenides, and phosphides of different transition metals as electrocatalysts. Doping of the transition metals within the host matrix is a good strategy to improve the electrocatalytic activity of the host material. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…While it is trivial to mention that the creation of new catalytic centers in Ga 2 O 3 through Fe is the reason for the electrocatalytic performance, the nonlinear and bell-shaped behavior of catalytic activity points to a more complex enabling mechanism. It is reported that transition-metal doping adjacent to catalytic centers (mostly electronegative elements such as oxygen or sulfur) in electrocatalysts can enhance its activity by lowering the hydrogen adsorption free energy (Δ G H ). Hence, the lattice inclusion of Fe while doping creates highly catalytic centers and lowers hydrogen adsorption free energy (Δ G H ) by weakening the bonds between Ga and O atoms in the lattice, resulting in a more favorable adsorption of proton and its subsequent reduction to H 2 . However, this still does not explain the modulation of catalytic activity with respect to doping content, as well as the bell-shaped behavior of the activity.…”
Section: Resultsmentioning
confidence: 99%
“…While it is trivial to mention that the creation of new catalytic centers in Ga 2 O 3 through Fe is the reason for the electrocatalytic performance, the nonlinear and bell-shaped behavior of catalytic activity points to a more complex enabling mechanism. It is reported that transition-metal doping adjacent to catalytic centers (mostly electronegative elements such as oxygen or sulfur) in electrocatalysts can enhance its activity by lowering the hydrogen adsorption free energy (Δ G H ). Hence, the lattice inclusion of Fe while doping creates highly catalytic centers and lowers hydrogen adsorption free energy (Δ G H ) by weakening the bonds between Ga and O atoms in the lattice, resulting in a more favorable adsorption of proton and its subsequent reduction to H 2 . However, this still does not explain the modulation of catalytic activity with respect to doping content, as well as the bell-shaped behavior of the activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is more difficult to discern this trend from the measurements on pure Ag or as-annealed Ag 95 Au 5 alloy due to the interference from the current densities associated with the oxidation of AgSH ads into Ag 2 S ads . There are also reports of enhanced proton and water reduction rates on heterogeneous catalysts composed of noble and/or transition metal sulfides [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…[1,2] They are useful in various fields such as energy storage, [3] CO 2 reduction, [4] water splitting, [5] photocatalytic degradation of dyes [6] and catalyst for the synthesis of aromatic aldehydes. [7] The optical, magnetic and electrical properties of metal sulfide nanoparticles can be enhanced by doping and the doped metal sulfide nanoparticles are useful for applications in solar cells, [8] bio-imaging, [9] supercapacitors, [10] hydrogen evolution, [11] photocatalytic reduction [12] and bactericides. [13] Sinsermsuksakul et al have synthesized Sb doped SnS thin films using atomic layer deposition and employed the doped thin films as absorber in solar cells.…”
Section: Introductionmentioning
confidence: 99%